Pressure Ulcer Rate in Multidisciplinary Hospital Units After Multifactorial Intervention: A Stepped-Wedge, Cluster Randomized Controlled Trial. Issue 3 (September 2018) - Jafary, Mohamadreza; Adibi, Hossin; Shayanfard, Kamran; Zohdi, Mehri; Godarzi, Zahra; Yaseri, Mehdi; Najafpour, Zhila
Abstract : Objectives: This study was conducted to measure the effectiveness of interventions in decreasing the rates of pressure ulcer in a general hospital setting. Methods: Sixteen units in a general hospitals in Iran participated in this stepped-wedge, cluster randomized controlled trial during a 45-week study period. This trial has a one-sided crossover design from control to intervention. The units were randomly assigned fulfilling entry criteria. After the approval by the governing board of hospital, the manipulative intervention, in addition to usual care, was implemented on patients with a Braden criterion of 14 or less. The primary outcome was ulcer specification (grade and location of ulcer), and the secondary outcome was the length of hospital stay. Results: A total of 18, 900 patients were admitted during the 45-week study period in the study units, of whom approximately 20% (3846 patients) were identified as high risk according to the items of Braden scale criteria during the admission assessment by nurses. The highest rate of PUs (80%) was in grade 2, and 16% of patients had grade 3 and 4 PUs. The ulcers of the skin overlying the sacrum and hip areas were the most common sites in the patients under study. The rates of PU in the control, training, and intervention phases were 5.49 (4.72–6.34), 5.68 (3.82–8.15), and 4.62 (3.87–5.47), respectively, per 1000 patient-days. Conclusions: The multifaceted intervention proposed by the present study has succeeded in reducing rate of pressure ulcer. Multifaceted programs based on training are appropriate ways to provide essential information to patients and their caregivers, which result in improvement of their participation in therapeutic process. We recommend hospitals to use these findings as a quality improvement plan for decreasing the rate of pressure ulcer.